Exploring strategy text and cases - Whittington, Richard 1958-; Regnér, Patrick; Angwin, Duncan 1953-; Johnson, Gerry; Scholes, Kevan (Pearson, 2020)
"We are delighted to offer this twelfth edition of Exploring Strategy. With sales of previous editions now well over one million worldwide, we believe we have a tried and tested product. Yet the strategy field is constantly changing. For this edition, therefore, we have thoroughly refreshed all chapters, with new concepts, new cases and new examples throughout. Here we would like to highlight three principal changes, while recalling some of the classic features of the book"--
Keywords: Strategisches Management; Unternehmensplanung; Strategie; Planung; Strategische Planung; Geschäftsplan; Strategisches Management / (DE-627)091393116 / (DE-STW)18029-0; Business planning; Strategic planning; Business planning / Case studies; Strategic planning / Case studies; Lehrbuch; Fallstudiensammlung